2006
DOI: 10.1136/bjo.2006.101675
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy with intravitreal triamcinolone: effect on uveitic cystoid macular oedema and treatment limitations

Abstract: Uveitic CME that is unresponsive to systemic immunosuppression and acetazolamide may improve after PPV with additional intravitreal triamcinolone application. The effect seems to be transient in many of the patients. Frequent complications were cataract formation and ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…The advantageous effect of pars plana vitrectomy (PPV) on CME has been regularly reported in the noncontrolled studies; large randomized trials have so far not been performed [50,51]. A randomized pilot study [52] (23 eyes) established that PPV had a beneficial effect on visual function and angiographic findings compared to a slighter effect of systemic treatment with steroids and immunosuppressants.…”
Section: Surgical Treatments For Inflammatory Cystoid Macular Edemamentioning
confidence: 96%
“…The advantageous effect of pars plana vitrectomy (PPV) on CME has been regularly reported in the noncontrolled studies; large randomized trials have so far not been performed [50,51]. A randomized pilot study [52] (23 eyes) established that PPV had a beneficial effect on visual function and angiographic findings compared to a slighter effect of systemic treatment with steroids and immunosuppressants.…”
Section: Surgical Treatments For Inflammatory Cystoid Macular Edemamentioning
confidence: 96%
“…In addition, immunosuppression may be required to improve inflammation and CME [10,11] . Pars plana vitrectomy has also been shown to improve CME and vision in selected cases [12][13][14] , and intravitreal bevacizumab was recently introduced as a further treatment option [15,16] . Roesel Injections of triamcinolone acetonide (TA) are most commonly given via the intravitreal (IVTA) or posterior periocular route, one of which is the orbital floor.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on visual outcomes of 20-gauge vitrectomy for uveitic eyes reported improvement in visual acuity in 48-82.8% after surgery for granulomatous and nongranulomatous uveitis [14,15,16,17] and improvement of more than 2 lines in 60-64% [15,40,41]. There are few reports on MIVS for uveitis, and most of them are small case series.…”
Section: Discussionmentioning
confidence: 99%